Beauty Is in the Eye of the Beholder: Research on the Mate Selection Preferences of the Contemporary Chinese Youth. - Yang, Jia; Zhang, Wenmin (Archives of Sexual Behavior, 2025)
This study analyzed how the objective conditions of potential mates and individual conditions affected the mate selection satisfaction of Chinese youth, with a focus on the moderating role of gender and the mediating effect of education. Using data from the 2021 China General Social Survey (N = 1767), this study incorporated correlation analysis, variance analysis, linear regression model and structural equation model, Key findings include: (1) Physical appearance (β = 0.25, p < 0.001) emerged as the strongest predictor of satisfaction, followed by income (β = 0.17,p < 0.001), homeownership (β = 0.14,p < 0.001), and education (β = 0.12, p < 0.001). (2) Gender played a significant moderating role: men preferred older mates while women prioritized higher income mates. (3) Education had a significant negative impact on satisfaction and a significant mediating effect on the negative impact of living environment on satisfaction, while also exhibiting a significant masking effect (suppressing the true relationship by the opposing indirect effect) on the positive impact of social trust on satisfaction. These results extended mate preference theories by demonstrating the existence of educational stratification in the Chinese marriage market.